Comparing Different Synthetic Talc as Fillers for Polyurethane Nanocomposites. Issue 1 (September 2016) - Dias, Guilherme; Prado, Manoela; Carone, Carlos; Ligabue, Rosane; Dumas, Angela; Le Roux, Christophe; Micoud, Pierre; Martin, François; Einloft, Sandra
Summary: This work presents the syntheses of PU nanocomposites, by in situ polymerization technique, using different synthetic talcs as inorganic filler. The fillers were obtained from two different hydrothermal treatments and composition (talc‐Mg and talc‐Ni). For nanocomposites syntheses 3% w/w of synthetic talc were added related to the weight of pure polymer. Samples were characterized by Fourier Transform Infrared Spectroscopy (FTIR), X‐Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) to understand the influence of the fillers syntheses and composition in morphological and thermal properties of the obtained nanocomposites. When talc‐Ni was used as filler, the resulting nanocomposite was intercalated while with talc‐Mg was exfoliated into the polyurethane matrix. Both fillers have increased the thermal properties of the polymer, but the exfoliated nanocomposite provided higher thermal stability.